The experimental of heat providing and cooling for electric generation by peltier. - ศิริกุล, ภาณุพงศ์; ปราโมทย์, พิพัฒน์; จานทอง, มนูศักดิ์ (Frontiers in Engineering Innovation Research, 2009)
This article presents the experiments and analyses results of heat providing and cooling system to increase efficiency in electricity generation of peltier plate by providing temperature to the peltier plate. Controlled the heat with electric current to the bar Heater via solid-state relays and uses thermocouple as a temperature measurements. For controlling use LabVIEW program together with PID Control Toolset and uses the interface card USB-6008 in order to communicating between computers and the process of heat providing to the peltier plate in the heat side. Use the heat sink for cooling from cold side of the peltier plate in order to obtain the electric power. The test results showed that the heat input which is controlled by PID controllers using the Kp0.298, Ti4.200, Td1.050, providing heat to a single module in hot side with temperatures of 68 degrees Celsius and transferred the heat with aluminum heat sink in cold side will cost the most Seebeck coefficient. Module position placement, double module type Ng provided the highest power